Characterization of CMOS-MEMS device for acetone vapor detection in exhaled breath - Rabih, A.A.S. (Institute of Electrical and Electronics Engineers Inc., 2015)
A MEMS vapor sensor for acetone detection in exhaled breath (EB) has been fabricated using 0.35 μm CMOS technology. Acetone vapor in EB is used as a non-invasive method for diabetes screening, which is currently conducted invasively by measuring blood glucose in blood. This paper studies the characterization of polysilicon piezoresistors, heater and temperature sensor embedded in the device. The measured resistances were found to be close to the modelled values within 1.1-6.8 error. Temperature coefficient of resistance (TCR) of the temperature sensor in a range of 25-100°C was found. TCR increases linearly with increasing the temperature and decreases linearly with decreasing the temperature. It was found to be 0.0033/°C for the increasing temperature and 0.0034/°C for the decreasing temperature, compared to 0.0038/°C reported in the literature, with an error of 13 and 10.5, respectively. © 2015 IEEE.